Tranformasi digital: efektivitas sistem e-registration dalam pendaftaran wajib pajak (npwp) - Lu'ai, Yusril Zam Zami (Maliki Interdisciplinary Journal, 2026)
Digital transformation in tax administration has become a strategic step to enhance the efficiency and transparency of public services. This study aims to analyze the effectiveness of the E-Registration system in the process of Taxpayer Identification Number (NPWP) registration in Indonesia. The research employs a descriptive quantitative approach, collecting data through surveys of prospective taxpayers and interviews with officials from the Directorate General of Taxes. The results indicate that the implementation of the E-Registration system has significantly improved service speed and reduced administrative barriers. However, challenges remain, such as limited digital literacy and technical issues related to network accessibility in certain regions. Overall, the system is considered effective in supporting the government’s digital transformation agenda, particularly in enhancing tax compliance and administrative convenience.